Boundary Crossing by a Community of Practice: Tibetan Buddhist Monasteries Engage Science Education - Worthman, Carol M.; Kruger, Ann Cale; Achat-Mendes, Cindy; Lhamo, Tashi; Wangyal, Rinchen; Gyatso, Gelek; Gray, Kelsey M. (Frontiers in Communication, 2021)
As a globalized world struggles with division and disinformation, engaging across difference has emerged as a major challenge to communication and collaborative action needed to address growing global challenges. As such, the initiative by Tibetan Buddhist leaders to incorporate western science in curricula for monastic education may serve as an important case study that illuminates the conditions and processes at work in genuine cultural outreach and exchange. That project, spearheaded in the Emory-Tibet Science Initiative (ETSI), involves reaching out across two quite different communities of practice, Tibetan Buddhism and science, and the willingness and ability of individuals to cross the boundaries between them. In the study reported here, we apply existing understandings of communities of practice and of learning mechanisms that mediate boundary crossing to probe for presence of conditions and processes that promote effective outreach among Tibetan Buddhist monastic students. We deploy analysis of qualitative survey, interview, and self-report data from monastic students shortly after ETSI began (2009) and after science education had been rolled out in the monasteries (2019) to, first, identify initial cultural conditions related to outreach and engagement with science, and, second, probe for post-rollout presence of boundary crossing learning mechanisms among monastic students which facilitate communication from one community of practice to another. We found a range of robust initial cultural conditions (e.g., perceived overlap in subjects and methods of inquiry), along with strong presence of mechanisms that facilitate boundary crossing (e.g., reflection, transformation) and operate through time. We observed cascading effects of these conditions and mechanisms on student engagement with science. Furthermore, interactions of these conditions and mechanisms allow monastic students to engage with science on their own Buddhist terms and to regard learning science as potentially beneficial rather than threatening to their personal or collective Buddhist goals.